1959
DOI: 10.1243/pime_proc_1959_173_052_02
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Temperature Strain Gauges

Abstract: This paper is restricted to a review of the work carried out in order to develop a strain gauge capable of operating at temperatures up to 1000°C with an inherent accuracy of ±5 per cent. A large number of resistance alloys were tested as unbonded long wires at room temperature and, from the results obtained, a small number were selected for further investigation, in the form of gauges, at high temperatures. The effects of factors such as metallurgical changes, geometric shape and long-term exposure on the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The gauge factor appeared to vary at rather less than 0·001 per cent per degC over the temperature range 20-600°C. These results were essentially in agreement with those reported in the earlier investigation (5).…”
Section: Fig 10 Short-term Performance Of Stabilized Karma Gaugessupporting
confidence: 94%
See 2 more Smart Citations
“…The gauge factor appeared to vary at rather less than 0·001 per cent per degC over the temperature range 20-600°C. These results were essentially in agreement with those reported in the earlier investigation (5).…”
Section: Fig 10 Short-term Performance Of Stabilized Karma Gaugessupporting
confidence: 94%
“…Characteristics of unbonded wires In view of their high temperature coefficients of resistance at elevated temperatures, the alloys of copper-nickel and chrome-iron tested during the earlier work (5) were not considered for the present application. Alloys of the nickelchromium series appeared suitable and initial tests were carried out on bright annealed Brightray C wires loosely wound on formers and cooled at various rates from IOOO°C.…”
Section: Gauge Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly for moderate plastic strains (up to 0.01 m/m), Kammer and Pardue 9 showed that alloys, such as annealed Constantan, Cupron, and Copel X, have a gage factor K = 2. Likewise Bertoldo 10,11 found that the gage factor of a single wire of various materials tends to 2 in the plastic range.…”
Section: The Gage Factor In the Plastic Rangementioning
confidence: 93%
“…This concept came from researches in which the main results were given in terms of experimentally obtained diagrams (ΔR/R) x (ɛ), as conceived by Bertodo (1959), for example. Observing Ohm's law, the resistance is given by Equation 4:…”
Section: Sensor Sensitivitymentioning
confidence: 99%